04 Construction and analysis of lair-1 over-expressed nk-92 cells. (5th December 2017) - Fu, Q; Sun, YF; Xue, JN; Piao, HL; Du, MR; Li, DJ
Abstract : Background: LAIR-1 can be triggered by collagen and its intracellular ITIMs are crucial for the inhibitory signal to NK cells. In order to investigate the regulation mechanisms of LAIR-1/collagen on NK cells, we aimed to construct LAIR-1 over-expressed NK-92 cells with which STATs related analysis was performed. Methods: Lentivirus-mediated transfection was used to construct LAIR-1 over-expressed NK-92 cells. The expression of LAIR-1 in the constructed NK-92 cells was identified by QPCR and Western blot analysis. Immunofluorescence test was also used to observe the efficiency of lentivirus-mediated expression of LAIR-1 in NK-92 cells. The LAIR-1 over-expressed NK-92 cells were cultured in the IL-2 free medium for 48 hours and then different concentrations of IL-2 were added into the culture system and the cells were collected after 30 mins. The expression of STAT1, p-STAT1, STAT4, and p-STAT4 were analysed by Western blot analysis. Results: QPCR and Western blot analysis results showed the over-expressed LAIR-1 in NK-92 cells. Immunofluorescence result showed high efficiency of LAIR-1 lentiviral infection. Western blot results showed IL-2 could increase the phosphorylation of STAT1 in a dose-dependent manner, but not STAT4. Conclusion: LAIR-1 over-expressed NK-92 cells were constructed successfully and the IL-2 treatment experiment showed different roles of STAT1 and STAT4 in the regulation of NK cells. Acknowledgements: Supported by a project grant from the Natural Science Foundation of Shandong Province (ZR2015JL027) and National Natural Science Foundation of China (81370730, 81571512, 81273200, and 31300751).